2016
DOI: 10.3389/fmicb.2016.01853
|View full text |Cite
|
Sign up to set email alerts
|

Production, Characterization, and Application of Bacillus licheniformis W16 Biosurfactant in Enhancing Oil Recovery

Abstract: The biosurfactant production by Bacillus licheniformis W16 and evaluation of biosurfactant based enhanced oil recovery (EOR) using core-flood under reservoir conditions were investigated. Previously reported nine different production media were screened for biosurfactant production, and two were further optimized with different carbon sources (glucose, sucrose, starch, cane molasses, or date molasses), as well as the strain was screened for biosurfactant production during the growth in different media. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 58 publications
6
26
2
1
Order By: Relevance
“…Hence, it may be conluded that the strain B. licheniformis Ali5 did not produce biopolymer but produced only biosurfactant. The viscosity of some biopolymers was studied and found to be around 43-21,535 cP [23]. These results are in accordance with some of the previously reported bacillus species [24][25][26].…”
Section: Media and Carbon Source Optimizationsupporting
confidence: 88%
See 3 more Smart Citations
“…Hence, it may be conluded that the strain B. licheniformis Ali5 did not produce biopolymer but produced only biosurfactant. The viscosity of some biopolymers was studied and found to be around 43-21,535 cP [23]. These results are in accordance with some of the previously reported bacillus species [24][25][26].…”
Section: Media and Carbon Source Optimizationsupporting
confidence: 88%
“…Band characteristics of the peptides were at 3323 cm −1 (NH stretching mode), and at 1629 cm −1 (stretching mode of CO-N bond); while the bands at 2957-2926, 2854, 1403, 1377 cm −1 reflected the aliphatic chains (-CH3, -CH2-) of the fractions, as described in Joshi et al [28]. It is concluded from the results that the biosurfactant is a cyclic lipopeptide, the infrared spectrum produced is quite similar to bacilli produced Surfactin and Lichenysin as reported previously [3,23].…”
Section: Partial Structural Identification Using Fourier Transform Insupporting
confidence: 80%
See 2 more Smart Citations
“…On this solid support, the secreted bacterial proteases could pre-hydrolyze the okara proteins, stimulating the lipopeptide biosynthesis [ 29 ]. Related to the lipopeptide amounts, it was also observed that isolate B. licheniformis W16 showed the highest biosurfactant activities, using either glucose or cane molasses as a carbon source [ 30 ].…”
Section: Introductionmentioning
confidence: 99%